2008
DOI: 10.1017/s1074070800002480
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Price Transmission in the Presence of a Major Food Safety Shock: Impact of H5N1 Avian Influenza on the Turkish Poultry Sector

Abstract: This article addresses the dynamic impact of the 2005 H5N1 avian influenza outbreak on the Turkish poultry sector. Contemporary time-series analyses with historical decomposition graphs are used to address differences in monthly price adjustments between market levels along the Turkish poultry supply channel. The empirical results show that price adjustments are asymmetric with respect to both speed and magnitude along the marketing channel. Results also reveal a differential impact of the exogenous shock on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 34 publications
4
18
1
Order By: Relevance
“…It is worth noting that the analysis of EPTs implicitly assumes that price transmission proceeds downward along the marketing channel. However, the direction of causality may be opposite (i.e., upward along the channel), particularly when other studies have found mixed evidence on this matter in different markets (e.g., Capps & Sherwell, ; Goodwin & Harper, ; Goodwin & Holt, ; Saghaian, Ozertan, & Spaulding, ; Tiffin & Dawson, ). Regardless the direction of causality, EPT values different than one, will point to imperfect competition or a breakdown in the transmission of price signals at specific levels of the marketing chain…”
Section: Resultsmentioning
confidence: 98%
“…It is worth noting that the analysis of EPTs implicitly assumes that price transmission proceeds downward along the marketing channel. However, the direction of causality may be opposite (i.e., upward along the channel), particularly when other studies have found mixed evidence on this matter in different markets (e.g., Capps & Sherwell, ; Goodwin & Harper, ; Goodwin & Holt, ; Saghaian, Ozertan, & Spaulding, ; Tiffin & Dawson, ). Regardless the direction of causality, EPT values different than one, will point to imperfect competition or a breakdown in the transmission of price signals at specific levels of the marketing chain…”
Section: Resultsmentioning
confidence: 98%
“…Some research on the characteristics of food markets suggests that these markets are typically oligopolistic (Sexton and Lavoie, 2001;Sheldon and Sperling, 2003), allowing the exercise of market power by downstream industries. It is not surprising that among the arguments 4 that have been provided to account for asymmetric price movements the most commonly cited is the presence of market power in retail and/or processing industries (see, for example, McCorriston et al, 1998McCorriston et al, , 2001.…”
Section: Asymmetric Price Transmission -Existing Theories and Empiricmentioning
confidence: 99%
“…For example, Saghaian, Ozertan, and Spaulding () and Hassouneh, Radwan, Serra, and Gil () identify supply shocks in terms of influenza outbreaks that threaten food security. Saghaian et al () study the Turkish poultry sector, whereas Hassouneh et al () investigate the Egyptian poultry sector. Both studies show a significant impact on vertical price transmission along the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The supply chain of less‐developed countries, in particular for poultry, has some specific characteristics such as a lack of appropriate storage facilities, relatively short production cycles in an environment characterized by high search, and processing costs (Chaudhry & Miranda, ). These features make poultry chains in less‐developed countries especially interesting for analyzing cost pass‐through dynamics (Chaudhry & Miranda, ; Hassouneh et al, ; S. S. Hosseini et al, ; Saghaian et al, ; Ukum, Molua, & Ake, ).…”
Section: Literature Reviewmentioning
confidence: 99%